A MUNDIALIZAÇÃO DO CAPITAL E A SUPERPOPULAÇÃO RELATIVA : uma análise sobre a reestruturação da força de trabalho nos países da OCDE, no período de 2000 a 2010 - Sousa, Nara Soares (2012)
Objective of this study is to analyze, under the aegis of the recent globalization of capital, the expansion of relative surplus population as a restructuring of the workforce, as well as its causes and its implications on the working class. The effects of globalization of capital and productive restructuring bring significant changes in the structure of the workforce worldwide. These changes extend continuously created competition for capital among workers for too few jobs. The called relative surplus population expansion comes in even in rich countries, and that are the result of measures taken to restore the capital. Neoliberal ideology posited as a way to bypass the capitalist crisis, which is configured in the falling rate of profit in the private sector combined with the fiscal crisis in the public sector, has directed the accumulation regime for the remuneration of creditors and shareholders. In this context , part of the capital is subtracted from the production process, contributing to the advancement of the process of deindustrialization and industrial relocation as a means of lowering costs of production and restore the rate of profit. Implications of these processes on the labor market show that it is directly influenced by the existence of overcrowding on the conditio sine qua non of capital accumulation.